Uma tentativa de mudança da prática de ensino de professores de inglês da escola pública de Arapiraca - Lima, Rosangela Nunes de (2014)
This doctoral research in Linguistics, within the research line of Applied Linguistics, concentrates its focus on the monitoring of three teachers from public schools in Arapiraca, two of them working in the urban area and the other one working in the rural area of the city. These teachers participated in a continuing education course which aimed to encourage the adoption of a culture of analysis of the practices performed in their classrooms, so they could reflect and possibly change these practices. The main objective of this research was to detect, describe and characterize their teaching practices, and their speeches when they take to their practices the discussions, readings and theories of the course, and how they reflect after the course, in order to understand the contribution of this reflective practice after the course for the construction of discourses and practices of teaching English that best fit the needs of people in their LE classrooms. The research is theoretically grounded as a qualitative-interpretative case study (ERICKSON, 1985; ANDRÉ, 2008), with a socio-historical approach, from studies of Vygotsky (1998); reflective practice of teachers, with the contribution of (FREIRE, 2002; PERRENOUD, 2002, and ALARCÃO, 2011), and scholars in the field of Linguistics and Applied Linguistics as (CAZDEN, 1988; CELANI, 2010, 2006; MOITA LOPES , 2006, 1996; BROWN, 2001; MONTE MÓR, 2010). The data that make up the corpus of the research were collected through different instruments which enabled to identify manifestations of the teachers on their teaching practice during and after the course. The results of the analysis were used to characterize the participating teachers‟s practices of teaching, as well as to observe theory in practice. The results showed that reflective practice involves not only theoretical or methodological knowledge, but also understanding and individual analysis, which takes place only with the desire for transformation of the teachers who are involved in a sociocultural, educational context, which is a particularity of the development of the teacher.